Re-Desain Lengan Robot 6 DOF Berdasarkan Benchmarking Menggunakan Permodelan 3D pada AutoDesk Inventor 2024 - Elvyra Danotti; Steven Fernando Chu; Handi Wilujeng Nugroho; Kurniawan Hamidi; Monika (Teknosia, 2025)
The industrial revolution 4.0 has encouraged the development of automation systems, including the 6 DOF robotic arm to enhance industrial production efficiency and effectiveness. This study aims to redesign a 6 DOF robotic arm based on benchmarking with Fanuc M-20iA and ABB IRB 2600 models using AutoDesk Inventor 2024. The method employed is benchmarking by comparing designs and specifications, followed by redesigning the Bill of Materials (BoM), Operation Process Chart (OPC), and assembly chart. The results show modifications such as redesigning the base into a square shape, adding rubber strips to the gripper, creating a separate panel for the motor driver and controller, and replacing the electromagnetic gripper with a mechanical one. The final design produces a simpler robotic arm with a production cost (HPP) of Rp105,554,924.00, which is more economical compared to similar products. The newly designed gripper is recommended for vertical object handling and positioning. Thus, the design successfully reduces maintenance costs, enhances precision, and maintains optimal performance for industrial applications.